Evolution of the Seasonality of Shigelloses - V. V. Shkarin; O. A. Chubukova (Эпидемиология и вакцинопрофилактика)
The seasonality of shigellosis (bacillary dysentery) from the 20th century till nowadays in the Niznhiy Novgorod Region was compared with the data on the Russian Federation. The year dynamics was characterized by the transformation of the peak month from July (in the beginning of the 20th century) to the autumn and winter period (in the end of the 20th and beginning of the 21st century). We demonstrated the different statistical features of the shigellosis seasonality and its variations during more than hundred years. The range of variations per month decreased almost 20 times, the seasonality index dropped 8.3 times, the seasonality coefficient decreased almost 4 times. Thus, the different parameters of the shigellosis epidemiology were exposed to the significant evolutionary shifts. We critically estimated the opinions of different scientists concerning the factors that can influence the year dynamics of the dysentery morbidity rates. We also showed the need of the profound and complex studies of the evolutionary changes of shigelloses by different professionals.